PENGARUH LINGKUNGAN EKSTERNAL TERHADAPMINAT BERWIRAUSAHA PADA MAHASISWAPENDIDIKAN EKONOMI DI FAKULTAS EKONOMIUNIVERSITAS NEGERI SURABAYA - MISBAKHUDDIN, AHMAD (Jurnal Pendidikan Tata Niaga (JPTN), 2013)
Entreprise is one of alternative choices when job rivalry goes heavily. But only partly of peoples put a high interest in entrepreneurship. Of course, it may be a deviance for university students in order to choose work for other people or build the own business. Actually, there is many factors can influence the entrepreneurship interest, the one is external environment. The purpose of this research is to find out whether external environment influence entrepreneurship interest of university students in Faculty of Economic in State University Of Surabaya. This research used quantitative phenomenological. The population is university students of Economic Education major. The sample are 160 respondents conducted by purposive sampling technique. The data was collected by questionnaires. Statistic descriptive was used to analyze the data. This research shows the unsignificant effect of caring pattern and curriculum to the entrepreneurship interest of university students with value of tcount as 0,859 and 0,734 and the signification value for each of them are 0,392 and 0,464. But the coeval group and mass media influence significantly with the value of tcount as 5,287 and 2,517 with the significant value for each of them are 0,000 and 0,013. The external enviroment influence as 33% toward the entrepreneurship interest simultaneously. Keyword: external environment, entrepreneurship interest.